+0

# (-1)^n+1 x n = 50

0
313
3

(-1)^n+1 x n = 50

Guest May 25, 2015

#1
+26402
+10

n = 51

$${\left(-{\mathtt{1}}\right)}^{{\mathtt{51}}}{\mathtt{\,\small\textbf+\,}}{\mathtt{1}}{\mathtt{\,\times\,}}{\mathtt{51}} = {\mathtt{50}}$$

.

Alan  May 26, 2015
Sort:

#1
+26402
+10

n = 51

$${\left(-{\mathtt{1}}\right)}^{{\mathtt{51}}}{\mathtt{\,\small\textbf+\,}}{\mathtt{1}}{\mathtt{\,\times\,}}{\mathtt{51}} = {\mathtt{50}}$$

.

Alan  May 26, 2015
#2
+91454
0

That is neat Alan

Melody  May 26, 2015
#3
+81022
+5

Notice that this wouldn't be too difficult to solve........the first term is either -1 or 1.....

Let's suppose it was 1.....then "n" would have to be even........rearranging the equation, we have

n = 50 - 1   = 49.......but this is a contradiction, because n is even

If n were odd, we would have {again, rearranging}

n = 50 + 1........and this must be the solution, because

(-1)^51 + 51 = 50     →  -1 + 51  = 50     ..... which is true.....!!!

CPhill  May 26, 2015

### 5 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details